HMGB1, IL-1α, IL-33 and S100 proteins: dual-function alarmins - Bertheloot, Damien (Cell Mol Immunol, 2017)
Our immune system is based on the close collaboration of the innate and adaptive immune systems for the rapid detection of any threats to the host. Recognition of pathogen-derived molecules is entrusted to specific germline-encoded signaling receptors. The same receptors have now also emerged as efficient detectors of misplaced or altered self-molecules that signal tissue damage and cell death following, for example, disruption of the blood supply and subsequent hypoxia. Many types of endogenous molecules have been shown to provoke such sterile inflammatory states when released from dying cells. However, a group of proteins referred to as alarmins have both intracellular and extracellular functions which have been the subject of intense research. Indeed, alarmins can either exert beneficial cell housekeeping functions, leading to tissue repair, or provoke deleterious uncontrolled inflammation. This group of proteins includes the high-mobility group box 1 protein (HMGB1), interleukin (IL)-1α, IL-33 and the Ca(2+)-binding S100 proteins. These dual-function proteins share conserved regulatory mechanisms, such as secretory routes, post-translational modifications and enzymatic processing, that govern their extracellular functions in time and space. Release of alarmins from mesenchymal cells is a highly relevant mechanism by which immune cells can be alerted of tissue damage, and alarmins play a key role in the development of acute or chronic inflammatory diseases and in cancer development.